PENINGKATAN HASIL BELAJAR PKn MELALUI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) BAGI SISWA KELAS VI SDN 4 NGRAHO KEDUNGTUBAN BLORA SEMESTER I TAHUN 2015 / 2016 - Nanik Maharani (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2016)
In this proses of lerning doing by researcher of students grade VI SDN 4Ngraho year 2015/2016 Kedungtuban Blora, researcher found a problem that is lowlearning result of students. Purpous of this research is for learnng result PKn of studentsgrade VI SDN 4 Ngraho Kedungtuban Blora year 2015/2016. Learning models ofNumbered Head Together (NHT). For example is learning that attractive. Studentsdevide become some groups, in one group 2-3 students researcher guide student forrow and make a group and a group ger a numbers. researcher give exam and a gruopdoing this exam. A gruop discus about this answear that real and make sure of groupcan answear this exam.researcher call one of group a number of students and call ofnumber must result of discus. Comment of another friends, and than researcher callanother number. From result data analysis can be concluded that with learning modelNHT to show high in of from condition beginning until with cycle II. Point ofaverage get 54 become 75 with high point 70 become 90 dan low point 40 become 60with point 30.Keyword : learning result, Number Head Together ( NHT)